Ocorrência de epidemia do mal das folhas em regiões de escape do Brasil - Furtado, Edson Luiz; Cunha, Antonio Ribeiro Da; Alvares, Clayton Alcarde; Bevenuto, João Alberto Zago; Passos, José Raimundo (Instituto Biológico, 2015)
ABSTRACT: In January and February 2013 occurred a South American leaf blight epidemic in regions considered as escape zones, causing concern to rubber tree growers and throughout the rubber industry. A possible adaptation of the fungus to escape zones was raised and the consistency of disease control by the use of the binomial: plants with uniform renewal of leaves + dry season, typical of the escape zones, was questioned. The aim of this work was to bring relevant information to the rubber growers about the interaction climate-pathogen-host and to compare normal climate (historical average) and climatic data of the occurrence period of epidemic (January and February 2013). We conclude that was not the pathogen that has adapted to rubber tree in drier conditions, typical in escape regions, but a more humid climate occurred in these drier regions during this period.

RESUMO: Entre janeiro e fevereiro de 2013 ocorreu uma epidemia de mal das folhas em regiões consideradas como de escape à doença, causando preocupações e indagações nos produtores de borracha e ao setor heveícola como um todo. Uma possível adaptação do fungo a essas zonas foi levantada e a consistência do controle da doença pela utilização do binômio plantas com troca uniforme das folhas + período seco, típicos de regiões de escape, foi questionada. O objetivo deste trabalho foi trazer informações importantes aos heveicultores sobre a interação clima-patógeno-hospedeiro e comparar variáveis de normais climatológicas (média histórica) e dados climáticos deste período de ocorrência da epidemia (janeiro e fevereiro de 2013). Concluiu-se que não foi o patógeno que se adaptou às plantas de seringueira em clima mais seco, nas regiões de escape, mas que o clima mais úmido ocorreu nessas regiões mais secas, nesse período.
Occurrence of South American leaf blight epidemic in escape zones of the Brazil
Keywords: rubber tree; climate; Microcyclus ulei; seringueira; clima; Microcyclus ulei